THE ANALYTICAL STUDY OF THE POROUS SILICON ELECTRICALCONDUCTIVITY - Haider, Adawiya J (Al-Nahrain Journal of Science, 2018)
In this approach we review the electrical conductivity of porous silicon (PS) within this frame work, we study the variation of (PS) conductivity as a function to the limiting parameters such as porosity and temperature. We interpret such conductivity and mobility depended on the properties of the PS layer and the quantum confinements effect in (PS).